UNIT 1F.4 Biochemical Analysis of Microbial Rhodopsins. Issue 1 (6th May 2016) - Maresca, Julia A.; Keffer, Jessica L.; Miller, Kelsey J.
Abstract : Ion‐pumping rhodopsins transfer ions across the microbial cell membrane in a light‐dependent fashion. As the rate of biochemical characterization of microbial rhodopsins begins to catch up to the rate of microbial rhodopsin identification in environmental and genomic sequence data sets, in vitro analysis of their light‐absorbing properties and in vivo analysis of ion pumping will remain critical to characterizing these proteins. As we learn more about the variety of physiological roles performed by microbial rhodopsins in different cell types and environments, observing the localization patterns of the rhodopsins and/or quantifying the number of rhodopsin‐bearing cells in natural environments will become more important. Here, we provide protocols for purification of rhodopsin‐containing membranes, detection of ion pumping, and observation of functional rhodopsins in laboratory and environmental samples using total internal reflection fluorescence microscopy. © 2016 by John Wiley & Sons, Inc.